2012
DOI: 10.1007/jhep01(2012)121
|View full text |Cite
|
Sign up to set email alerts
|

Young diagrams, Brauer algebras, and bubbling geometries

Abstract: We study the 1/4 BPS geometries corresponding to the 1/4 BPS operators of the dual gauge theory side, in N = 4 SYM. By analyzing asymptotic structure and flux integration of the geometries, we present a mapping between droplet configurations arising from the geometries and Young diagrams of the Brauer algebra. In particular, the integer k classifying the operators in the Brauer basis is mapped to the mixing between the two angular directions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…A basis for the local operators which organizes the theory using the quantum numbers of the global symmetries was given in [13,14]. Another basis, employing projectors related to the Brauer algebra was put forward in [15] and developed in a number of interesting works [16][17][18][19][20][21][22]. For the systems we are interested in, the most convenient basis to use is provided by the restricted Schur polynomials.…”
Section: Jhep03(2016)156mentioning
confidence: 99%
“…A basis for the local operators which organizes the theory using the quantum numbers of the global symmetries was given in [13,14]. Another basis, employing projectors related to the Brauer algebra was put forward in [15] and developed in a number of interesting works [16][17][18][19][20][21][22]. For the systems we are interested in, the most convenient basis to use is provided by the restricted Schur polynomials.…”
Section: Jhep03(2016)156mentioning
confidence: 99%
“…The result of these studies is a basis of local operators that also diagonalizes the free field two point function. These bases have been useful for exploring giant gravitons [13,14,15,16,17,18,54,20,21,22,23] and new background geometries [24,25,26,27,28,29,30,31,32,33,34,35] in AdS/CFT [36], as well as for the computations of anomalous dimensions in large N but non-planar limits [37,38,39,40,41,42,43]. Elements in the basis are labeled by Young diagrams.…”
Section: Discussionmentioning
confidence: 99%
“…Because such conserved charges correspond to parameters of the dual physics, it would be helpful to conduct an analysis in the string/gravity side. In [39] we have studied a correspondence between 1/4 BPS operators and 1/4 BPS geometries, where it was shown that the geometries are characterised by an integer that has the same upper bound as the integer k (: recall k ≤ min(m, n)). This fact might be a clue to solve the operator mixing dual to geometries.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This leads to considering the restriction 2), which determines the mixing structure. Denoting an irreducible representation of B N (1, 2) by γ 3 , the necessary condition for the non-zero mixing is that the M γ γ 2 ,γ 3 , which is given by the same form as (39), is non-zero. Denoting the number of boxes in a partition α by n(α), we find that n(δ) and n(ζ) take 0, 1, 2, and n(ǫ) and n(κ) take 0, 1.…”
Section: More General Differential Operatorsmentioning
confidence: 99%